NUCLIDES COMPOSITION OF EXPERIMENTAL POWER REACTOR (RDE) SPENT FUEL - Kristina Kristina; Amir Hamzah; Muhammad Subekti; Menik Ariani (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2020)
The management of spent fuel is an issue of safety for Indonesia in the phase of designing RDE. Several studies regarding spent fuel are limited by geometrical characteristics and number of nuclides library. Therefore, different methodologies utilizing MCNPX2.6.0 were applied to get better information for further research. In this study, a single fuel pebble containing UO2, was burned using 5 cycles of multi-pass loading scheme for 1080 days to obtain the same energy as RDE’s core, which is about 79.90 GWd/MTU. The multiplication factor k-inf decreased at each cycle and stopped at 1.14575. The calculation results in the nuclides composition of the spent fuel after 1080 days of burning and 5 years of cooling containing 241 nuclides consist of 21 actinides and 220 nonactinides. Actinides with the highest activity of 8.96 Ci is with mass of 0.0867 g, whose half-life time is 14 years long. Nonactinides with the highest activity of 4.47 Ci is  with mass of 0.0514 g, whose half-life time is 30.17 years long. The total activity of spent fuel pebble is 22.9 Ci with total mass of 5.28 g. The mass and activity data of each nuclide contained in the spent pebble will be used in the future research for performing safety analysis of the spent fuel storage tank.Keywords: Nuclides composition, Pebble, Spent fuel, RDE, MCNPX